Preparation method and application of low-shrinkage compact ceramic
By adding sintering aids to the ceramic master powder and sintering at high temperature, the problems of high shrinkage and high-temperature sintering energy consumption are solved, and the preparation of low shrinkage, accurate net size and high-performance ceramics are achieved.
Patent Information
- Application Number
- CN202411991047.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing ceramic preparation methods have high shrinkage problems during the sintering process, resulting in inaccurate ceramic dimensions, affecting the mechanical and physical properties, and at the same time, high-temperature sintering consumes energy and is costly.
The sintering aid is added to the master powder and covered on the ceramic blank. The sintering temperature and shrinkage rate of the ceramic are performed at a temperature higher than the melting point of the sintering aid are used to reduce the sintering temperature and shrinkage rate of the ceramic by using the liquid phase sintering and evaporation-coagulation sintering process of the sintering aid.
The low shrinkage rate and accurate net size of the ceramic are achieved, which reduces sintering temperature and energy consumption, improves the density, strength and mechanical properties of the ceramics, while reducing costs and environmental impacts.
Smart Images

Figure CN119751094A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special ceramics, and in particular relates to a preparation method and application of low-shrinkage dense ceramics. Background Art
[0002] Sintering is a crucial link in the ceramic preparation process. It is a process in which the surface area of a porous ceramic body is reduced, the porosity is reduced, and the performance is improved at high temperature. As densification proceeds, the ceramic body generally shrinks greatly. The shrinkage rate of dense ceramics after sintering is usually more than 15%, which is not conducive to obtaining samples of precise size. On the one hand, subsequent processing is often required; on the other hand, high shrinkage often brings obvious strain, affecting mechanical properties and corresponding physical properties. Therefore, researchers have carried out a lot of work to obtain quasi-net-size ceramics. Among them, pressure sintering (especially hot pressing sintering) is effective in the preparation of quasi-net-size ceramics. However, it has the following limitations: 1) expensive sintering equipment is required; 2) the damage to the equipment is large; 3) the energy consumption is large. Therefore, it is particularly important to develop a new, low-cost method for preparing low-shrinkage quasi-net-size ceramics.
[0003] Buried firing is a common sintering method for many functional ceramics. Usually, mother powder with the same composition as the ceramic is used as buried firing powder during the buried firing process. Especially for ceramics with easily volatile elements (such as lead, bismuth, lithium ion, etc.), buried firing is conducive to the uniformity of the sintering temperature field and the uniformity of the composition, thereby improving the performance.
[0004] Generally, ceramics need high-temperature sintering to be dense, which will result in high energy consumption and increased costs. In recent years, with the development trend of energy conservation and emission reduction, people have adopted various methods to reduce the sintering temperature of ceramics in order to achieve low-temperature sintering. Generally, there are several methods to reduce the sintering temperature of ceramics: (1) Adding sintering aids such as low-melting point oxides or low-softening point glass phases. This method is the most common. If the sintering temperature is significantly reduced, it is generally necessary to add more sintering aids, which will lead to a significant deterioration of the performance of the ceramics, and its shrinkage rate after sintering is often higher. (2) Using chemical or physical methods to reduce the particle size of the initial powder and prepare ultrafine powders (such as nanopowders), thereby reducing the sintering temperature of microwave dielectric ceramics. However, this method is complex and costly, and sometimes also faces performance deterioration and higher shrinkage. (3) Finding ceramics with inherently low sintering temperatures, without adding sintering aids and without the need for ultrafine powders, can achieve low-temperature sintering. However, there are very few ceramics with inherently low sintering temperatures, and generally their performance has certain limitations, making it difficult to meet application requirements.
[0005] For specific ceramics, it is usually difficult to lower the sintering temperature. Adding sintering aids often reduces the sintering temperature, which will lead to deteriorated performance and higher shrinkage. Although hot pressing sintering can obtain net-size ceramics, in addition to the above-mentioned disadvantages, in order to protect the sintering equipment, an inert atmosphere or a reducing atmosphere is usually required, which increases the cost on the one hand and is not suitable for oxide ceramics on the other hand. Therefore, it is particularly urgent to research and develop a ceramic sintering method that can not only reduce the sintering temperature, but also obtain quasi-net-size and excellent performance. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a preparation method and application of low shrinkage dense ceramics. The method of the present invention can not only reduce the sintering temperature, but also obtain ceramics with quasi-net size and excellent performance.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention:
[0009] The invention provides a method for preparing low-shrinkage dense ceramics, comprising adding a sintering aid into a mother powder, then covering the mother powder containing the sintering aid on a ceramic green body, and sintering at a temperature higher than the melting point of the sintering aid to obtain the low-shrinkage dense ceramics.
[0010] In the present invention, a sintering aid is added to the mother powder as a calcining powder, and the mother powder with the same composition as the ceramic is used as one of the calcining powder components during the calcining process. 6.4 Ln3Z 1.4 Ta 0.6 O 12 When the solid electrolyte ceramic is used as the base, the mother powder is Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Powder, mother powder plus sintering aid is sintering powder.
[0011] The principle of the present invention is:
[0012] 1. In addition to the powder with the same composition as the green body, the sintering powder also contains sintering aid powder. When the temperature rises during the sintering process, the sintering powder appears in liquid phase or higher partial pressure, which is beneficial to liquid phase sintering and evaporation-condensation sintering during the green body sintering process, thereby accelerating the sintering rate. On the one hand, it reduces the sintering temperature to achieve low-temperature sintering, and on the other hand, it inhibits the volatilization of volatile substances in the green body and reduces its shrinkage rate.
[0013] 2. During the sintering process, as the sintering temperature increases, the strength of the green body will decrease, and the gravity of the buried powder will play a role in hot pressing sintering, greatly reducing the shrinkage rate. On the other hand, the liquid phase in the buried powder may fill the voids in the green body, reducing its radial shrinkage rate. The combination of the two can significantly reduce the shrinkage rate of the ceramic and achieve a quasi-net size effect.
[0014] 3. Due to the novel buried firing method of the present invention, the effects of low-temperature sintering and hot-pressing sintering are achieved, and the growth of grains can be significantly inhibited, thereby providing a practical method for obtaining fine-grained, high-performance ceramics.
[0015] The temperature higher than the melting point of the sintering aid is 50-400° C. higher than the melting point of the sintering aid, that is, the sintering is performed at 50-400° C. higher than the melting point of the sintering aid.
[0016] The sintering aid is selected from at least one of lithium-containing compounds, boron-containing compounds, copper-containing compounds, gallium-containing compounds, tungsten-containing compounds, compounds containing both copper and boron, molybdenum-containing compounds and bismuth-containing compounds.
[0017] The above sintering aids can reduce the sintering temperature of ceramics, reduce energy consumption, save costs, and reduce environmental impact. The above sintering aids can also rearrange the powder particles in the green body to achieve a tighter spatial stacking, thereby promoting material densification and improving the density and strength of the material. The above sintering aids can act as grain refiners, inhibiting the abnormal growth of grains, making the microstructure of the ceramic more uniform and fine, thereby improving its mechanical properties (such as hardness and fracture toughness) and thermal stability.
[0018] Exemplarily, the lithium-containing compound is selected from at least one of lithium oxide (Li2O), lithium hydroxide, lithium carbonate (Li2CO3), lithium nitrate (LiNO3), lithium sulfate (Li2SO4), lithium oxalate (Li2C2O4) and lithium acetate (C2H3LiO2), and the lithium hydroxide is solid lithium hydroxide (LiOH) or lithium hydroxide monohydrate (LiOH·H2O).
[0019] Exemplarily, the boron-containing compound is selected from at least one of boron oxide (B2O3) and boric acid (H3BO3); and / or
[0020] The copper-containing compound is selected from at least one of copper oxide (CuO), cuprous oxide (Cu2O), copper chloride (CuCl2), copper sulfate (CuSO4) and copper nitrate (Cu(NO3)2); and / or
[0021] The gallium-containing compound is selected from at least one of gallium oxide (Ga2O3), gallium chloride (GaCl3) and gallium nitrate (Ga(NO3)3).
[0022] Exemplarily, the tungsten-containing compound is selected from at least one of tungsten oxide (WO3), calcium tungstate (CaWO4), sodium tungstate (Na2WO4) and lithium tungstate (Li2WO4); and / or
[0023] The molybdenum-containing compound is selected from at least one of molybdenum oxide (MoO3), calcium molybdate (CaMoO4), sodium molybdate (Na2MoO4) and lithium molybdate (Li2MoO4); and / or
[0024] The bismuth-containing compound is selected from at least one of bismuth oxide (Bi2O3), bismuth molybdate (Bi2MoO6), bismuth tungstate (Bi2WO6) and bismuth nitrate (Bi(NO3)3).
[0025] Exemplarily, the copper and boron containing compound is BaCuB2O5.
[0026] The sintering aid is 5-50% of the mother powder mass. The sintering aid has a significant impact on the performance of the ceramic, including improving density, improving mechanical properties, affecting thermal conductivity, optimizing microstructure, controlling sintering temperature and affecting resistivity. The present invention can optimize the performance of the ceramic and meet specific application requirements by reasonably controlling the amount of sintering aid added.
[0027] During the sintering, the heat preservation time is 0.5-3 hours.
[0028] The second technical solution of the present invention:
[0029] The present invention also provides a low-shrinkage dense ceramic prepared according to the method, the shrinkage of which is lower than 5% and the relative density can reach 98.3%.
[0030] The third technical solution of the present invention:
[0031] The invention also provides the use of the ceramic with low shrinkage rate in the preparation of solid electrolytes, dielectric materials and pressure-sensitive materials.
[0032] Compared with the prior art, the present invention has the following advantages and technical effects:
[0033] (1) The present invention introduces a sintering aid into the buried sintering powder, which effectively reduces the sintering temperature of the ceramic, thereby achieving energy saving and cost reduction;
[0034] (2) The shrinkage rate of the ceramics prepared by the present invention is less than 5%, which is much lower than the shrinkage rate of traditional solid-phase sintering and buried-firing ceramics, which is conducive to obtaining ceramics with precise dimensions. In addition, the stress introduced by the high shrinkage rate during the sintering process is greatly reduced, which is conducive to improving the performance of the ceramics.
[0035] (3) The preparation method provided by the present invention significantly reduces the sintering temperature, which is beneficial to inhibiting the grain growth of the prepared ceramics, thereby preparing fine-grained or even nano-ceramics;
[0036] (4) The preparation method provided by the present invention significantly reduces the sintering temperature, which is beneficial to suppress the volatilization of volatile components in the prepared ceramics, thereby ensuring the stoichiometric ratio, improving performance on the one hand, and reducing emissions on the other hand, which is beneficial to energy conservation, emission reduction and cost reduction;
[0037] (5) The preparation method of the present invention requires simple equipment, simple process, low cost, and has good economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0039] Figure 1 The master powder in Example 1 and the low shrinkage Li in Example 1 6.4 Ln3Z 1.4 Ta 0.6 O 12 Solid electrolyte ceramics and Li in Comparative Example 1 6.4 Ln3Z 1.4 Ta 0.6 O 12 XRD spectrum of the solid electrolyte ceramics;
[0040] Figure 2 The low shrinkage Li in Example 1 6.4 Ln3Z 1.4 Ta 0.6 O 12 Solid electrolyte ceramic (a) and Li in Comparative Example 1 6.4 Ln3Z 1.4 Ta 0.6 O 12 (b) SEM image of the solid electrolyte ceramic. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0047] All raw materials used in the embodiments of the present invention are purchased from the market or synthesized by existing technology. As an example, CuO, Li2O, Li2CO3, H3BO3, B2O3, WO3, MoO3, and Ga2O3 are all purchased from Sinopharm Chemical Reagent Co., Ltd., and sintering aids BaCuB2O5, CaWO4, and Li2WO4 are all synthesized by solid phase reaction method. Among them, BaCuB2O5 is prepared by weighing and ball milling raw materials BaCO3, CuO, and H3BO3 according to chemical proportions (ball milling process: deionized water is used as the ball milling medium, the grinding balls are zirconium oxide balls, planetary ball milling is used, the ball milling speed is 380 rpm, and the ball milling time is 8 hours); the ball-milled slurry is dried at 65°C and sieved, and the sieve is 120 mesh; after sieving, it is pre-calcined at 700°C for 2 hours to obtain BaCuB2O5 powder. The synthesis method of CaWO4 is as follows: the raw materials CaCO3 and WO3 are weighed according to the chemical ratio and mixed by ball milling (ball milling process: deionized water is used as the ball milling medium, the grinding balls are zirconium oxide balls, planetary ball milling is used, the ball milling speed is 380 rpm, and the ball milling time is 6 hours); the ball milled slurry is dried at 85°C and sieved, the sieve is 120 mesh; after sieving, it is pre-calcined at 800°C for 2 hours to obtain CaWO4 powder. The synthesis method of Li2WO4 is as follows: the raw materials Li2CO3 and WO3 are weighed according to the chemical ratio and mixed by ball milling (ball milling process: deionized water is used as the ball milling medium, the grinding balls are zirconium oxide balls, planetary ball milling is used, the ball milling speed is 380 rpm, and the ball milling time is 6 hours); the ball milled slurry is dried at 85°C and sieved, the sieve is 120 mesh; after sieving, it is pre-calcined at 600°C for 2 hours to obtain Li2WO4 powder.
[0048] In the present invention, shrinkage refers to the linear shrinkage of ceramic diameter, which is the ratio of the linear shrinkage of the ceramic green body during the high-temperature densification process to the initial size. The calculation method is linear shrinkage (%) = (initial diameter size - diameter size after sintering) / initial diameter size × 100%.
[0049] Ceramic green body refers to the volume of the green body after the ceramic is formed and before sintering, which has been dried. This volume is the volume of the green body after the ceramic raw materials are mixed and formed (such as by grouting, dry pressing, isostatic pressing, etc.), and the excess water is removed, so that the green body reaches a certain degree of dryness. In the present invention, ceramic green body refers to the ceramic green body after pressing.
[0050] An embodiment of the present invention provides a method for preparing low-shrinkage dense ceramics, wherein a sintering aid is added to the buried powder, and then the buried powder containing the sintering aid is covered on a ceramic body, and sintered at a temperature 50-400°C higher than the melting point of the sintering aid to obtain low-shrinkage dense ceramics.
[0051] In the present invention, a mother powder with the same composition as the ceramic is used as one of the ingredients of the calcined powder during the calcination process. 6.4 Ln3Z 1.4 Ta 0.6 O 12 When the solid electrolyte ceramic is used as the base, the mother powder is Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Powder, mother powder plus sintering aid is sintering powder.
[0052] The present invention first mixes, ball-mills, dries, pre-burns, and presses ceramic raw material powders into cylindrical ceramic bodies; then places the cylindrical ceramic bodies on the mother powder of the support plate, and covers the cylindrical ceramic bodies with burying powder containing a sintering aid; and sintering at a temperature 50-400°C higher than the melting point of the sintering aid to obtain low-shrinkage dense ceramics with quasi-net dimensions. The low-shrinkage dense ceramics of the present invention can be used in solid electrolyte ceramics, dielectric ceramics, and varistor ceramics, all with good effects. The present invention has a simple scheme, a simple process flow, and low cost, is suitable for large-scale commercial application and promotion, and has good application value.
[0053] The present invention introduces a low-melting-point sintering aid into the buried sintering powder, which not only reduces the sintering temperature of the ceramic, but also greatly reduces the shrinkage rate of the ceramic (below 5%), thereby obtaining a ceramic with a quasi-net size; more importantly, the performance of the ceramic is improved, and the ceramic is applied to solid electrolyte ceramics, dielectric ceramics, and varistor ceramics, and good results have been achieved. The present invention is suitable for the preparation of high-performance materials such as high-performance solid electrolytes, dielectric materials, and varistor materials.
[0054] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in the art and are not the focus of the present invention.
[0055] The technical solution of the present invention is further illustrated by the following embodiments.
[0056] Example 1 Low shrinkage Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Preparation of solid electrolyte ceramics based on
[0057] (1) According to Li 6.4 Ln3Z 1.4 Ta 0.6 O 12The raw materials Li2CO3, La2O3, ZrO2, and Ta2O5 powders were mixed in a chemical ratio, deionized water was used as the ball milling medium, the grinding balls were zirconium oxide balls, a planetary ball mill was used, the ball milling speed was 300 rpm, and the ball milling time was 8 hours; the ball-milled slurry was dried at 85°C and sieved with a 120-mesh screen; after sieving, it was pre-calcined at 950°C for 3 hours to obtain cubic garnet phase Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Powder;
[0058] (2) pressing a portion of the powder obtained in step (1) at 100 MPa to form a ceramic body;
[0059] (3) The other part of the powder obtained in step (1) is used as a master powder, and the master powder (i.e., Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 powder) containing 10% by weight of a sintering aid CuO-Li2O (CuO-Li2O has a melting point of 830° C. The preparation method of CuO-Li2O is as follows: Li2O and CuO are weighed in a molar ratio of 1:1, and mixed by ball milling; the ball milling process is as follows: deionized water is used as a ball milling medium, the grinding balls are zirconium oxide balls, a planetary ball mill is used, the ball milling speed is 380 rpm, and the ball milling time is 6 hours; the ball milled slurry is dried at 85° C. and then sieved, the sieve is 120 mesh, and CuO-Li2O powder is obtained after sieving), and the sintered powder is obtained after being evenly mixed;
[0060] (4) Cover the ceramic body prepared in step (2) with calcined powder and keep it at 1000°C for 3 hours to obtain a Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Based solid electrolyte ceramics.
[0061] The Li prepared in this example 6.4 Ln3Z 1.4 Ta 0.6 O 12 Performance of solid electrolyte ceramics: mother powder in this embodiment, Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 The XRD spectrum of the solid electrolyte ceramics is shown in Figure 1 , the low shrinkage Li in this embodiment 6.4 Ln3Z 1.4 Ta 0.6 O 12 The SEM image of the solid electrolyte ceramic is shown in Figure 2 In (a), it can be seen that the crystal structure is cubic garnet single phase, the relative density is 95.8%, the shrinkage is 4.3%, and the ionic conductivity tested according to the standard GB / T 37253-2018 (the same below) is 1.59×10 -3 S / cm.
[0062] Comparative Example 1Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Preparation of solid electrolyte ceramics based on
[0063] (1) Prepare Li according to the method of step (1) in Example 1 6.4 Ln3Z 1.4 Ta 0.6 O 12 Powder;
[0064] (2) pressing the powder obtained in step (1) into a ceramic body at 100 MPa;
[0065] (3) The ceramic body prepared in step (2) was kept at 1250° C. for 3 hours to obtain Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Based solid electrolyte ceramics.
[0066] The Li prepared in this comparative example 6.4 Ln3Z 1.4 Ta 0.6 O 12 Performance of solid electrolyte ceramics: Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 The XRD spectrum of the solid electrolyte ceramics is shown in Figure 1 In this comparative example, Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 The SEM image of the solid electrolyte ceramic is shown in Figure 2 In (b), it can be seen that the main crystal phase is cubic garnet phase and a small amount of tetragonal garnet phase, and there are more La2Zr2O7 impurities, with a relative density of 78.5%, a shrinkage rate of 15.3%, and an ionic conductivity of 2.64×10 -4 S / cm.
[0067] Example 2 Preparation of Low Shrinkage BaO-Sm2O3-4.5TiO2-based Microwave Dielectric Ceramics
[0068] (1) The raw materials BaCO3, Sm2O3, and TiO2 powders are mixed according to the chemical ratio of BaO-Sm2O3-4.5TiO2, and deionized water is used as the ball milling medium, the grinding balls are zirconium oxide balls, and a planetary ball mill is used. The ball milling speed is 150 rpm and the ball milling time is 12 hours; the ball-milled slurry is dried at 85°C and sieved with a 120-mesh screen; after sieving, it is pre-calcined at 1100°C for 3 hours to obtain a new type of BaO-Sm2O3-4.5TiO2 tungsten bronze phase powder;
[0069] (2) pressing a portion of the powder obtained in step (1) at 100 MPa to form a ceramic body;
[0070] (3) The other part of the powder obtained in step (1) is used as a mother powder, 10% by weight of a sintering aid BaCuB2O5 (melting point 850° C.) is added thereto, and the mixture is mixed evenly to obtain a sintered powder;
[0071] (4) Cover the ceramic body prepared in step (2) with calcined powder and keep it at 900°C for 3 hours to obtain a low-shrinkage BaO-Sm2O3-4.5TiO2-based microwave dielectric ceramic.
[0072] The properties of the BaO-Sm2O3-4.5TiO2-based microwave dielectric ceramics prepared in this embodiment: a new tungsten bronze single phase, a relative density of 98.3%, a shrinkage rate of 3.8%, wherein the dielectric properties: a dielectric constant ε=81.3 and a dielectric loss tanδ=0.0004 at a frequency of 1 MHz tested according to the standard GB / T 5594.4-2015 (the same below); a dielectric constant ε=81.1 and a dielectric loss tanδ=0.00025 at a frequency of 3 GHz tested according to the standard GB / T 5597-1999 (the same below).
[0073] Comparative Example 2 Preparation of BaO-Sm2O3-4.5TiO2-based microwave dielectric ceramics
[0074] (1) preparing a BaO-Sm2O3-4.5TiO2 novel tungsten bronze phase powder according to the method of step (1) in Example 2;
[0075] (2) pressing the powder obtained in step (1) into a ceramic body at 100 MPa;
[0076] (3) The ceramic body prepared in step (2) is kept at 1350° C. for 3 hours to obtain a BaO-Sm2O3-4.5TiO2-based microwave dielectric ceramic.
[0077] The properties of the BaO-Sm2O3-4.5TiO2-based microwave dielectric ceramics prepared in this comparative example are: a new tungsten bronze single phase, a relative density of 96.1%, a shrinkage rate of 16.8%, and dielectric properties: dielectric constant ε=82.0 and dielectric loss tanδ=0.0005 at a frequency of 1MHz, and dielectric constant ε=81.3 and dielectric loss tanδ=0.00032 at a frequency of 3GHz.
[0078] Comparative Example 3 Preparation of BaO-Sm2O3-4.5TiO2-based microwave dielectric ceramics
[0079] (1) preparing a BaO-Sm2O3-4.5TiO2 novel tungsten bronze phase powder according to the method of step (1) in Example 2;
[0080] (2) adding 10% by weight of a sintering aid BaCuB2O5 to the powder obtained in step (1), and mixing them evenly to obtain a corresponding powder;
[0081] (3) pressing the powder obtained in step (2) into a ceramic body at 100 MPa;
[0082] (4) The ceramic body prepared in step (3) is kept at 950° C. for 3 hours to obtain a BaO-Sm2O3-4.5TiO2-based microwave dielectric ceramic.
[0083] The properties of the BaO-Sm2O3-4.5TiO2-based microwave dielectric ceramics prepared in this comparative example are: new tungsten bronze phase and glass phase, relative density of 97.2%, shrinkage rate of 17.2%, including dielectric properties: dielectric constant ε=82.5 and dielectric loss tanδ=0.0015 at a frequency of 1MHz, dielectric constant ε=80.7 and dielectric loss tanδ=0.00052 at 3GHz.
[0084] Since the sintering aid is added when preparing the ceramic body in this comparative example, although the sintering temperature of the ceramic is reduced to a certain extent, ceramics with low shrinkage cannot be obtained, and the dielectric loss is significantly increased due to the introduction of a large amount of sintering aid.
[0085] Example 3 Preparation of Low Shrinkage ZnO-Based Varistor Ceramics
[0086] (1) weighing chemical raw materials ZnO, Bi2O3, Sb2O3, Co3O4, MnCO3, NiO, Cr2O3 and Al(OH)3 according to the chemical ratio, and grinding the corresponding powders with deionized water as the ball mill, using zirconium oxide balls as the grinding balls, using a planetary ball mill, the ball milling speed is 150 rpm, and the ball milling time is 12 hours; the ball-milled slurry is dried at 85° C. and then sieved with a 120-mesh screen to obtain ZnO-based varistor ceramic powder;
[0087] (2) pressing a portion of the powder obtained in step (1) at 100 MPa to form a ceramic body;
[0088] (3) The other part of the powder obtained in step (1) is used as a master powder, and 20% by weight of a sintering aid Bi2O3-MoO3 (Bi2O3-MoO3 has a melting point of 700°C, and the preparation method of Bi2O3-MoO3 is as follows: Bi2O3 and MoO3 are weighed and mixed by ball milling in a molar ratio of 1:3; the ball milling process is as follows: deionized water is used as the ball milling medium, the grinding balls are zirconium oxide balls, a planetary ball mill is used, the ball milling speed is 380 rpm, and the ball milling time is 6 hours; the ball-milled slurry is dried at 85°C and sieved with a 120-mesh screen; the sieved powder is pre-calcined at 600°C for 2 hours to obtain Bi2O3-MoO3 powder), and the mixture is mixed evenly to obtain calcined powder;
[0089] (4) Covering the ceramic body prepared in step (2) with calcined powder, keeping the temperature at 900° C. for 3 hours, and obtaining a ZnO-based varistor ceramic with low shrinkage.
[0090] The properties of the ZnO-based varistor ceramics prepared in this embodiment are as follows: relative density is 97.4%, shrinkage is 3.7%, varistor coefficient α=90, leakage current I L =0.08μA / cm 2 .
[0091] Comparative Example 4 Preparation of ZnO-based varistor ceramics
[0092] (1) preparing ZnO-based varistor ceramic powder according to the method of step (1) in Example 3;
[0093] (2) pressing the powder obtained in step (1) into a ceramic body at 100 MPa;
[0094] (3) The ceramic body prepared in step (2) is kept at 1300° C. for 3 hours to obtain a ZnO-based varistor ceramic.
[0095] The properties of the ZnO-based varistor ceramics prepared in this comparative example are as follows: relative density is 95.7%, shrinkage is 17.6%, varistor coefficient α=75, leakage current I L =0.18μA / cm 2 .
[0096] Example 4 Preparation of Low Shrinkage BaTiO3-Based Dielectric Ceramics
[0097] (1) weighing chemical raw materials BaTiO3, MgO, Nb2O5, Mn3O4 and Y2O3 according to the chemical ratio, and grinding the corresponding powders with deionized water as the ball milling medium, zirconia balls as the grinding balls, and planetary ball milling at a ball milling speed of 200 rpm for 8 hours; drying the ball-milled slurry at 85° C. and sieving it with a sieve of 120 mesh to obtain BaTiO3-based dielectric ceramic powder;
[0098] (2) pressing a portion of the powder obtained in step (1) at 100 MPa to form a ceramic body;
[0099] (3) The other part of the powder obtained in step (1) is used as a mother powder, 20% by weight of a sintering aid BaCuB2O5 is added thereto, and the mixture is mixed evenly to obtain a calcined powder;
[0100] (4) Covering the ceramic body prepared in step (2) with calcined powder and keeping it at 950° C. for 3 hours to obtain a BaTiO 3 -based dielectric ceramic with low shrinkage.
[0101] The properties of the BaTiO3-based dielectric ceramics prepared in this embodiment are as follows: relative density is 98.6%, shrinkage is 3.6%, and average grain size is 285nm; at a frequency of 1kHz, the room temperature dielectric constant ε=2282 and the dielectric loss tanδ=0.0075, and the dielectric constant does not change by more than 15% relative to 25°C in the temperature range of -55-125°C, and its temperature characteristics meet the requirements of capacitor X7R.
[0102] Comparative Example 5 Preparation of BaTiO3-based dielectric ceramics
[0103] (1) preparing BaTiO3-based dielectric ceramic powder according to the method in step (1) of Example 4;
[0104] (2) pressing the powder obtained in step (1) into a ceramic body at 100 MPa;
[0105] (3) The ceramic body prepared in step (2) is kept at 1320° C. for 3 hours to obtain a BaTiO 3 -based dielectric ceramic.
[0106] The properties of the BaTiO3-based dielectric ceramics prepared in this comparative example are as follows: relative density is 96.9%, shrinkage is 17.7%, and average grain size is 2167nm; at a frequency of 1kHz, the room temperature dielectric constant ε=2482 and the dielectric loss tanδ=0.012, and the maximum change of the dielectric constant relative to 25°C in the temperature range of -55-125°C is more than 38%, and its temperature characteristics cannot meet the capacitor X7R requirements.
[0107] Example 5 Preparation of Low Shrinkage BaTiO3-Based Dielectric Ceramics
[0108] (1) preparing BaTiO3-based dielectric ceramic powder according to the method in step (1) of Example 4;
[0109] (2) pressing a portion of the powder obtained in step (1) at 100 MPa to form a ceramic body;
[0110] (3) using another part of the powder obtained in step (1) as a mother powder, adding 5% by weight of a sintering aid BaCuB2O5, and mixing them evenly to obtain calcined powder;
[0111] (4) Covering the ceramic body prepared in step (2) with calcined powder and keeping it at 1050° C. for 3 hours to obtain a BaTiO 3 -based dielectric ceramic with low shrinkage.
[0112] The properties of the BaTiO3-based dielectric ceramics prepared in this embodiment are as follows: relative density is 96.3%, shrinkage is 4.2%, and average grain size is 356nm; at a frequency of 1kHz, the room temperature dielectric constant ε=2326 and the dielectric loss tanδ=0.0087, and the maximum change of the dielectric constant relative to 25°C in the temperature range of -55-125°C is 15.8%, and its temperature characteristics basically meet the requirements of the capacitor X7R.
[0113] Example 6 Preparation of Low Shrinkage BaTiO3-Based Dielectric Ceramics
[0114] (1) preparing BaTiO3-based dielectric ceramic powder according to the method in step (1) of Example 4;
[0115] (2) pressing a portion of the powder obtained in step (1) at 100 MPa to form a ceramic body;
[0116] (3) adding 50% of sintering aid BaCuB2O5 to the other part of the powder obtained in step (1), mixing well to obtain calcined powder;
[0117] (4) Covering the ceramic body prepared in step (2) with calcined powder and keeping it at 900° C. for 3 hours to obtain a BaTiO 3 -based dielectric ceramic with low shrinkage.
[0118] The properties of the BaTiO3-based dielectric ceramics prepared in this embodiment are as follows: relative density is 97.2%, shrinkage is 3.3%, and average grain size is 268nm; at a frequency of 1kHz, the room temperature dielectric constant ε=1978 and the dielectric loss tanδ=0.0135, and the dielectric constant does not change by more than 15.0% relative to 25°C in the temperature range of -55-125°C, and its temperature characteristics meet the requirements of capacitor X7R.
[0119] Example 7 Preparation of Low Shrinkage BaTiO3-Based Dielectric Ceramics
[0120] (1) preparing BaTiO3-based dielectric ceramic powder according to the method in step (1) of Example 4;
[0121] (2) pressing a portion of the powder obtained in step (1) at 100 MPa to form a ceramic body;
[0122] (3) The other part of the powder obtained in step (1) is used as a master powder, and 20% by weight of a sintering aid CaWO4-Li2WO4 (the melting point of CaWO4-Li2WO4 is 740°C, and the preparation method of CaWO4-Li2WO4 is as follows: CaWO4-Li2WO4 weighs CaWO4 and Li2WO4 according to a molar ratio of 1:1, and mixes them by ball milling. The ball milling process is as follows: deionized water is used as the ball milling medium, the grinding balls are zirconium oxide balls, a planetary ball mill is used, the ball milling speed is 300 rpm, and the ball milling time is 4 hours; the ball-milled slurry is dried at 85°C and then sieved with a 120-mesh screen; the sieved powder is pre-calcined at 600°C for 2 hours to obtain CaWO4-Li2WO4 powder), and the mixture is mixed evenly to obtain calcined powder;
[0123] (4) Covering the ceramic body prepared in step (2) with calcined powder and keeping it at 1100° C. for 3 hours to obtain a BaTiO 3 -based dielectric ceramic with low shrinkage.
[0124] The properties of the BaTiO3-based dielectric ceramics prepared in this embodiment are as follows: relative density is 97.6%, shrinkage is 3.6%, and average grain size is 475nm; at a frequency of 1kHz, the room temperature dielectric constant ε=2197 and the dielectric loss tanδ=0.0086, and the dielectric constant does not change by more than 15.0% relative to 25°C in the temperature range of -55-125°C, and its temperature characteristics meet the requirements of capacitor X7R.
[0125] Example 8 Preparation of Low Shrinkage BaTiO3-Based Dielectric Ceramics
[0126] (1) preparing BaTiO3-based dielectric ceramic powder according to the method in step (1) of Example 4;
[0127] (2) pressing a portion of the powder obtained in step (1) at 100 MPa to form a ceramic body;
[0128] (3) The other part of the powder obtained in step (1) is used as a master powder, and 10% by weight of a sintering aid Bi2O3-Ga2O3 (the melting point of Bi2O3-Ga2O3 is 795°C. The preparation method of Bi2O3-Ga2O3 is as follows: weigh Bi2O3 and Ga2O3 according to a molar ratio of 1:1, and mix them by ball milling. The ball milling process is as follows: deionized water is used as the ball milling medium, the grinding balls are zirconia balls, a planetary ball mill is used, the ball milling speed is 300 rpm, and the ball milling time is 6 hours; the ball-milled slurry is dried at 85°C and then sieved with a sieve of 120 mesh; after sieving, Bi2O3-Ga2O3 powder is obtained), and the mixture is mixed evenly to obtain sintered powder;
[0129] (4) Covering the ceramic body prepared in step (2) with calcined powder and keeping it at 900° C. for 3 hours to obtain a BaTiO 3 -based dielectric ceramic with low shrinkage.
[0130] The properties of the BaTiO3-based dielectric ceramics prepared in this embodiment are as follows: relative density is 94.1%, shrinkage is 3.1%, and average grain size is 428nm; at a frequency of 1kHz, the room temperature dielectric constant ε=1869 and the dielectric loss tanδ=0.0106, and the dielectric constant does not change by more than 15.0% relative to 25°C in the temperature range of -55-125°C, and its temperature characteristics meet the requirements of capacitor X7R.
[0131] It can be seen from the above embodiments and comparative examples that for electrolyte ceramics, varistors, microwave dielectric ceramics, and capacitor dielectric ceramics, the preparation method provided by the present invention has the following advantages: (1) Compared with the traditional sintering method, not only the sintering temperature is greatly reduced, but also the performance is significantly improved. More importantly, the shrinkage rate is greatly reduced (less than 5%), and high-performance ceramics with quasi-net size are obtained; (2) Compared with the ordinary low-temperature sintering method, not only the sintering temperature is slightly reduced, but also because no sintering aid is directly added to the ceramic, the performance is better, and more importantly, the shrinkage rate is lower. In summary, the method provided by the present invention is expected to be applied to the corresponding fields.
[0132] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing low shrinkage dense ceramics, characterized in that: A sintering aid is added to the mother powder, and then the mother powder containing the sintering aid is covered on the ceramic green body, and sintered at a temperature higher than the melting point of the sintering aid to obtain the low shrinkage rate dense ceramic.
2. The method for preparing a low shrinkage dense ceramic according to claim 1, characterized in that: The sintering aid is selected from at least one of lithium-containing compounds, boron-containing compounds, copper-containing compounds, gallium-containing compounds, tungsten-containing compounds, compounds containing both copper and boron, molybdenum-containing compounds and bismuth-containing compounds.
3. The method for preparing a low shrinkage dense ceramic according to claim 2, characterized in that: The lithium-containing compound is selected from at least one of lithium oxide, lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium oxalate and lithium acetate.
4. The method for preparing a low shrinkage dense ceramic according to claim 2, characterized in that: The boron-containing compound is selected from at least one of boron oxide and boric acid; and / or The copper-containing compound is selected from at least one of copper oxide, cuprous oxide, cupric chloride, copper sulfate and copper nitrate; and / or The gallium-containing compound is selected from at least one of gallium oxide, gallium chloride and gallium nitrate.
5. The method for preparing low shrinkage dense ceramics according to claim 2, characterized in that: The tungsten-containing compound is selected from at least one of tungsten oxide, calcium tungstate, sodium tungstate and lithium tungstate; and / or The molybdenum-containing compound is selected from at least one of molybdenum oxide, calcium molybdate, sodium molybdate and lithium molybdate; and / or The bismuth-containing compound is selected from at least one of bismuth oxide, bismuth molybdate, bismuth tungstate and bismuth nitrate.
6. The method for preparing low shrinkage dense ceramics according to claim 2, characterized in that: The copper and boron containing compound is BaCuB2O5.
7. The method for preparing low shrinkage dense ceramics according to claim 1, characterized in that: The sintering aid is 5-50% of the mass of the mother powder.
8. The method for preparing low shrinkage dense ceramics according to claim 1, characterized in that: During the sintering, the heat preservation time is 0.5-3 hours.
9. A low shrinkage dense ceramic, characterized in that: The low shrinkage dense ceramic is prepared by the preparation method according to any one of claims 1 to 8, and the shrinkage rate of the low shrinkage dense ceramic is less than 5%.
10. Use of the low shrinkage dense ceramic according to claim 9 in the preparation of solid electrolytes, dielectric materials and varistor materials.
Citation Information
Cited By
Buried powder for sintering lithium garnet type electrolyte and method for preparing lithium garnet type electrolyte by using buried powder
CN117263701A
A lithium garnet type electrolyte sintering embedding powder and a method for preparing a lithium garnet type electrolyte using the embedding powder
CN117263701B